PsycEXTRA Dataset 2005
DOI: 10.1037/e583042012-001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-recorded video and closed circuit television testimony by adult sexual assault complainants on jury decision-making: An experimental study

Abstract: ForewordSexual assault is regarded as one of the most serious crimes in our society. Perpetrators can receive lengthy sentences if successfully convicted and victims are often left traumatised both physically and psychologically. In 2003 the Australian Institute of Criminology interviewed 6677 women of whom four percent reported being the victim of sexual violence in the last 12 months and 11 percent had been a victim in the past five years. Despite condemnation of this crime another Institute study of 141 sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…First, prosecutors were concerned that the use of the video-medium may detract from the persuasiveness of the evidence. This contrasts with research findings on child video testimony (see Davies, 1999) and the few studies on adult testimony that suggest any effects on credibility judgments and case outcome are negligible (Landstrom, Granhag, & Hartwig, 2005;Taylor & Joudo, 2005). Second, like police officers, prosecutors perceive the use of pre-recorded evidence improves the process for rape complainants (Westera et al, 2011a).…”
mentioning
confidence: 78%
“…First, prosecutors were concerned that the use of the video-medium may detract from the persuasiveness of the evidence. This contrasts with research findings on child video testimony (see Davies, 1999) and the few studies on adult testimony that suggest any effects on credibility judgments and case outcome are negligible (Landstrom, Granhag, & Hartwig, 2005;Taylor & Joudo, 2005). Second, like police officers, prosecutors perceive the use of pre-recorded evidence improves the process for rape complainants (Westera et al, 2011a).…”
mentioning
confidence: 78%
“…Research has demonstrated that a judgement of credibility is more likely to be based on personal beliefs and attitudes than what a witness says. In a study involving 210 members of the public who participated in 18 mock trials Taylor and Joudo (2005) found that despite watching the same testimony juror opinions about credibility varied greatly and was mostly influenced by demographics, beliefs, expectations and attitudes about how a 'real' victim of rape would behave. In part this is evidenced by the common trends in verdicts amongst different demographic groups.…”
Section: Rape Myths and Juror Decision-makingmentioning
confidence: 98%
“…Jury attitudes are known to be a significant factor in conviction rates, through direct acquittals and 'up-stream' through defence decision-making regarding pleas and prosecutors' decisions to proceed with a case or not (see Brown et al 2007;Lievore 2004a). Major studies have analysed jury decision-making in sexual assault trials and confirmed that jurors typically make decisions with reference to a range of extra-legal factors, including rape myths, gender stereotypes, inferences drawn about the complainant or defendant and attitudes towards violence against women generally (see Ellison and Munro 2009;Taylor 2007;Temkin and Krahé 2008;Taylor and Joudo 2005). The inability of statutory reform to displace from the criminal justice process rape myths and community attitudes that support or minimise violence against women is likely to be a significant factor contributing to low conviction rates in rape cases.…”
Section: Falling Rape Conviction Rates: Some Explanations and Responsesmentioning
confidence: 99%